Na trilha dos Kariri: implicações dos processos de comunicação na disseminação dos sistemas agroflorestais por camponeses/as cearenses - Lucena, Milene Madeiro de (2012)
Under the emergence of thinking about the challenges and problems related to social and environmental sustainability in semiarid Ceará and its principal focus the role of communication processes in the environmental context, this paper investigates the case of the spread of agroforestry systems( SAF's) production among peasant families in Cariri in southern Ceará. The starting point of the study are Kariri records about the people whose culture is marked by a spirituality deeply rooted in the relationship with nature, passed by the processes of oral communication. The / the peasants / as agroforestry today are seen here as the inheritors of this culture. In light of this reality, we investigate the complex web of mediations that the relationship between communication , culture and politics articulated, so that communication is seen from the sociality, recognizing the strategic importance of communication in the affirmation of identity and autonomy of people, shifting the axis of the discussion of the means for mediation. Thus, we discuss how the processes of communication about the spread of the SAF's for peasants/Cariri in the community and contribute to ecological sustainability of the households surveyed and their natural environment.